Melatonin Modulates the GABAergic Response in Cultured Rat Hippocampal Neurons - Xin-Ping Cheng; Hao Sun; Zeng-You Ye; Jiang-Ning Zhou (Elsevier, 2012)
In the present study, we investigated the effect of melatonin on the GABA-induced current (IGABA) and GABAergic miniature inhibitory postsynaptic currents (mIPSCs) in cultured rat hippocampal neurons using the whole-cell patch-clamp technique. We found that melatonin rapidly and reversibly enhanced IGABA in a dose-dependent manner, with an EC50 of 949 μM. Melatonin markedly enhanced the peak amplitude of a subsaturating IGABA but not that of a saturating IGABA. Interestingly, melatonin was effective only when GABA and melatonin were applied together. Furthermore, the effect of melatonin on IGABA was voltage-independent and did not change the ion selectivity of the GABAA receptor. The melatonin enhancement on IGABA can not be blocked by luzindole, a melatonin receptor antagonist, indicating that melatonin-induced IGABA enhancement was not via activation of its own membrane receptors. However, this enhancement may be mediated via high-affinity benzodiazepine sites as it was inhibited by the classical benzodiazepine antagonist flumazenil, suggesting an allosteric modulation of melatonin by binding to the sites of GABAA receptors. In addition, melatonin increased both amplitude and frequency of GABAergic mIPSCs, indicating that melatonin enhances GABAergic inhibitory transmission. Hence, our observation that melatonin has an enhancing effect on the GABAergic system may implicate a potential pathway for the neuroprotective effects of melatonin. Keywords:: melatonin, GABAA receptor, GABAergic miniature inhibitory postsynaptic current (mIPSC), whole-cell patch-clamp technique, hippocampal neuron